Theory of fuzzy computation - Syropoulos, Apostolos (USA Springer, 2014)
The book provides the first full length exploration of fuzzy computability. It describes the notion of fuzziness and present the foundation of computability theory. It then presents the various approaches to fuzzy computability. This text provides a glimpse into the different approaches in this area, which is important for researchers in order to have a clear view of the field. It contains a detailed literature review and the author includes all proofs to make the presentation accessible. Ideas for future research and explorations are also provided. Students and researchers in computer science and mathematics will benefit from this work. --
1. Introduction -- 2. A Précis of classical computability theory -- 3. Elements of fuzzy set theory -- 4. On fuzzy turing machines -- 5. Other fuzzy models of computation -- Appendices.
Includes bibliographical references (pages 145-153) and indexes.
Keywords: Fuzzy logic; Computer science